The Influence of Attractiveness, Facilities and Accessibility on Visiting Interest in Sawangan Village, Airmadidi District, North Minahasa Regency - Grasheylla Zefanya; Rine Kaunang; Grace A. J. Rumagit (International Journal of Economics, Business and Innovation Research, 2025)
Tourism is a vital sector for the global economy, including Indonesia. North Sulawesi is famous for its various kinds of natural beauty starting from mountains, hills, forests, beaches, lakes, islands, cultural tourism, and many other beauties Waruga or ancient burial place of the megalithic era in Minahasa. Waruga is included in the category of special interest tourism (unique) so that it has its own charm that makes some local and foreign tourists come specifically to visit to find out about Waruga. This makes Waruga attractive for tourists who want to understand local culture. This study aims to determine the effect of attractiveness, facilities and accessibility on visiting interest in Waruga attractions in Sawangan Village, Airmadidi District, North Minahasa Regency. Data collection methods by interview using questionnaires to all respondents in the last 3 months. This study involved 70 respondents who were visitors. The data analysis method uses a quantitative descriptive method using the SEM-PLS application, which in this study uses Smart-PLS 4.0. The results showed that facilities have a significant effect on visiting interest in Waruga Sawangan Tourism Objects. while attractiveness and accessibility have an insignificant effect on visiting interest in Waruga Sawangan Tourism Objects.